Analysis of radiation protective properties of polystyrene-based composite materials - Prokhorenko, E.M.; Lytvynenko, V.V.; Zakharchenko, A.A.; Khazhmuradov, M.A.; Sokolov, S.A.; Prokhorenko, T.G.; Ben, A.P. (Вопросы атомной науки и техники, 2021)
Polystyrene-metal composite materials were manufactured. Composite materials are made of polystyrene, which has been reinforced with highly dispersed powder-like aluminum. Tungsten or steel powder was applied as a radiation shielding additive. The radiation-protective characteristics of composite materials were studied using sources of ionizing radiation ²⁴¹Am and ¹⁵²Eu. Calculations of the relative attenuation of the absorbed dose of gamma radiation for protective materials with different mass composition have been performed. A comparison of the protective characteristics obtained experimentally and found by numerical methods is carried out. Hardness values were measured for composites with different component compositions. An increase in hardness with an increase in the amount of a metal component is shown. Були виготовлені полістирол-металеві композиційні матеріали, виготовлені з полістиролу, який був армований високодисперсним порошковим алюмінієм. Порошок вольфраму або сталі застосовували як радіаційно-захисну добавку. Радіаційно-захисні характеристики композиційних матеріалів досліджувалися за допомогою джерел іонізуючого випромінювання ²⁴¹Am і ¹⁵²Eu. Виконано розрахунки відносного ослаблення поглиненої дози гамма-випромінювання для захисних матеріалів із різним масовим складом. Проведено порівняння захисних характеристик отриманих експериментально і знайдених чисельними методами. Виконувався вимір значень твердості для композитів з різним компонентним складом. Показано збільшення твердості при збільшенні кількості металевої складової. Были изготовлены полистирол-металлические композиционные материалы, из полистирола, который был армирован высокодисперсным порошковым алюминием. Порошок вольфрама или стали применяли как радиационно-защитную добавку. Радиационно-защитные характеристики композиционных материалов исследовались при помощи источников ионизирующего излучения ²⁴¹Am и ¹⁵²Eu. Выполнены расчеты относительного ослабление поглощенной дозы гамма-излучения для защитных материалов с различным массовым составом. Проведено сравнение защитных характеристик полученных экспериментально и найденных численными методами. Выполнялось измерение значений твердости для композитов с различным компонентным составом. Показано увеличение твердости при увеличении количества металлической компоненты.